The Contribution of Digitalization to FDI Inflows – Private Investment Nexus in Advanced Countries - Van Bon Nguyen (Scientific Annals of Economics and Business, 2025)
Foreign direct investment (FDI) is crucial for economic advancement as it brings in physical capital, facilitates technology transfer, and promotes innovation. Concurrently, private investment stands as a fundamental driver of economic growth. The emergence of digital technology offers nations fresh prospects to cut costs, decrease emissions, and move towards a more sustainable, environmentally friendly economy. Does digitalization contribute to FDI inflows – private investment nexus in advanced countries? We provide the answer by applying the two-step system and difference GMM estimators to explore the effects of FDI, digitalization, and their interaction terms on private investment in 37 advanced countries from 2010 to 2023. The findings note that FDI crowds out private investment, but digitalization and interaction terms promote it. Furthermore, labor force increases private investment, while inflation decreases it. These results propose that advanced countries can adopt suitable policy strategies to maximize the benefits of FDI and digitalization for enhancing private investment.